2007
DOI: 10.1007/s00421-007-0403-1
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of energy demand in the new olympic windsurf board: Neilpryde RS:X®

Abstract: The aim of this study was to evaluate the energy demands of sailing the new Neilpryde RS:X Ò Olympic windsurf board. Ten skilled male subjects performed an exhaustive incremental treadmill test to determine their maximal physiological parameters. Thereafter, four tests were performed in a randomised order using two wind conditions, light [2-4 ms -1 (4-8 knots)] and strong: [9-11 ms -1 (16-22 knots)]. Oxygen consumption ( _ VO 2 ; ml min -1 kg -1 ), blood lactate concentration ([la] b , mmol l -1 ), and time sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
4
32
0
1
Order By: Relevance
“…The cardiorespiratory and blood lactate responses reported in the present study while using the new pumping technique are very closely aligned to those recently published by Castagna et al (2007) who studied a cohort of 10 French and Spanish international level windsurfers under similar wind velocity conditions. Accordingly, it is confirmed that sail pumping on the new Olympic RS:X board is associated with a high requirement on both aerobic (80% max) and anaerobic metabolic pathways.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The cardiorespiratory and blood lactate responses reported in the present study while using the new pumping technique are very closely aligned to those recently published by Castagna et al (2007) who studied a cohort of 10 French and Spanish international level windsurfers under similar wind velocity conditions. Accordingly, it is confirmed that sail pumping on the new Olympic RS:X board is associated with a high requirement on both aerobic (80% max) and anaerobic metabolic pathways.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the different sail area and board characteristics of the RS:X compared to the Mistral board [bigger sail (9.5 vs. 7.4 m 2 ), shorter (2.86 vs. 3.70 m) and wider board (93 vs. 63 cm)] also made sailors to develop a new pumping technique (Castagna et al 2007). Sailors claim that implementation of the new technique has made their boards sail faster and at a closer angle relative to the direction of the wind (better pointing angle ability relative to the wind).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparable or greater values for metabolic response have been observed in boardsailing by De Vito et al (1996& 1997, and more recently, Castagna et al (2007;2008) reported oxygen uptake values of 65 ml*kg -1 *min -1 , or above 80% of VO 2 max, with heart rates above 90% of HRmax and serum lactate exceeding 10 mmol*l -1 in elite Olympic board sailors when recorded during highly taxing conditions on water (characterized by light wind and down-wind sailing where immense sail pumping (i.e. manual repetitive movements with the rig) contributes as a main factor to propulsion).…”
Section: On-water Assessmentsmentioning
confidence: 51%
“…Estudos apontam as diversas exigências necessárias para a prática da vela, como: demandas de força, equilíbrio, coordenação, resistência, nutrição adequada, além de boas condições psicológicas para interpretar adequadamente ações do vento e do mar, tomar decisões rápidas, e manter a concentração e o foco de atenção (SLATER; TAN, 2007;DUARTE, 2007;MACKIE;LEGG, 1999;DAUTY et al, 2006;BERNARDI et al, 2007;CUNNINGHAM;HALE, 2007;LÉGER et al, 2007;PARDAL;SPURWAY, 2007;VALLEJO;ROSIQUE;GONZÁLEZ-MORO, 2008). Somado a isso, também se torna necessária uma boa atenção em tarefas individuais e simultâneas, estando estas relacionadas à capacidade do velejador em automatizar tarefas (ABERNETHY et al, 2007).…”
Section: Característica E Demandas Relacionadas à Velaunclassified